Radiation therapy for superficial inguinal lymph node metastases from ovarian clear cell carcinoma and associated inguinal hernia - Ishibashi, Naoya; Maebayashi, Toshiya; Nishimaki, Haruna; Okada, Masahiro (Translational Cancer Research, 2018)
About 3% of ovarian cancer (OC) metastases reportedly involve inguinal lymph nodes, but little published data on their radiosensitivity is available. Here, we report a 53-year-old woman with clear cell OC and left inguinal, supra-inguinal and obturator lymph node metastases (LNMs), and a huge, unresectable mass of adherent inguinal nodes. After standard hysterectomy, bilateral salpingo-oophorectomy, omentectomy, and pelvic lymphadenectomy, she underwent various chemotherapy regimens over 12 months, as the inguinal mass enlarged. Radiotherapy was subsequently successful but complicated by an inguinal hernia. Combined cytoreductive surgery, inguinal metastasectomy, and radiotherapy may be appropriate for patients with OC with inguinal LNMs.